Intravaginal lactic acid gel versus oral metronidazole for treating women with recurrent bacterial vaginosis: the VITA randomised controlled trial - Ross, Jonathan D. C.; Brittain, Clare; Anstey Watkins, Jocelyn; Kai, Joe; David, Miruna; Ozolins, Mara; Jackson, Louise; Abdali, Zainab; Hepburn, Trish M.; Griffiths, Frances; Montgomery, Alan; Daniels, Jane; et al. (BMC women's health, 2023)
Background Bacterial vaginosis is a common and distressing condition for women. Short-term antibiotic treatment is usually clinically effective, but recurrence is common. We assessed the effectiveness of intravaginal lactic acid gel versus oral metronidazole for treating recurrent bacterial vaginosis. Methods We undertook an open-label, multicentre, parallel group, randomised controlled trial in nineteen UK sexual health clinics and a university health centre. Women aged ≥ 16 years, with current bacterial vaginosis symptoms and a preceding history of bacterial vaginosis, were randomised in a 1:1 ratio using a web-based minimisation algorithm, to 400 mg twice daily oral metronidazole tablets or 5 ml once daily intravaginal lactic acid gel, for 7 days. Masking of participants was not possible. The primary outcome was participant-reported resolution of symptoms within 2 weeks. Secondary outcomes included time to first recurrence of symptoms, number of recurrences and repeat treatments over 6 months and side effects. Results Five hundred and eighteen participants were randomised before the trial was advised to stop recruiting by the Data Monitoring Committee. Primary outcome data were available for 79% (204/259) allocated to metronidazole and 79% (205/259) allocated to lactic acid gel. Resolution of bacterial vaginosis symptoms within 2 weeks was reported in 70% (143/204) receiving metronidazole versus 47% (97/205) receiving lactic acid gel (adjusted risk difference -23·2%; 95% confidence interval -32.3 to -14·0%). In those participants who had initial resolution and for whom 6 month data were available, 51 of 72 (71%) women in the metronidazole group and 32 of 46 women (70%) in the lactic acid gel group had recurrence of symptoms, with median times to first recurrence of 92 and 126 days, respectively. Reported side effects were more common following metronidazole than lactic acid gel (nausea 32% vs. 8%; taste changes 18% vs. 1%; diarrhoea 20% vs. 6%, respectively). Conclusions Metronidazole was more effective than lactic acid gel for short-term resolution of bacterial vaginosis symptoms, but recurrence is common following both treatments. Lactic acid gel was associated with fewer reported side effects. Trial registration ISRCTN14161293 , prospectively registered on 18 th September 2017.